1994
DOI: 10.1128/jb.176.5.1434-1442.1994
|View full text |Cite
|
Sign up to set email alerts
|

The Myxococcus xanthus dsg gene product performs functions of translation initiation factor IF3 in vivo

Abstract: The amino acid sequence of the Dsg protein is 50%o identical to that of translation initiation factor IF3 of Escherichia coli, the product of its infC gene. dsg mutants are able to initiate the developmental process, but their development goes awry when the cells have formed loose asymmetric aggregates, at about 6 to 10 h. These mutants are unable to transcribe a particular set of developmentally regulated genes (3). The dsg mutation also affects the cells during vegetative growth. Mutants form compact, heaped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Interestingly, unlike other bacterial species (29,30), loss of this IF3 is not lethal in F. diplosiphon due to the presence of a second, redundant, highly divergent IF3 that has no apparent role in light regulation. We show that a wide range of bacteria and photosynthetic eukaryotes possess the potential to produce multiple IF3s.…”
Section: Significancementioning
confidence: 88%
See 1 more Smart Citation
“…Interestingly, unlike other bacterial species (29,30), loss of this IF3 is not lethal in F. diplosiphon due to the presence of a second, redundant, highly divergent IF3 that has no apparent role in light regulation. We show that a wide range of bacteria and photosynthetic eukaryotes possess the potential to produce multiple IF3s.…”
Section: Significancementioning
confidence: 88%
“…Measurements were made in both red light (RL) and green light (GL). infCa mRNA levels were normalized by using ribosomal RNA values for each sample (13 signal (Dsg) plays a role in both translation initiation and developmental processes, such as controlling sporulation and fruiting body development (30,39). In the purple nonsulfur bacterium Rhodobacter sphaeroides, the IF3-like protein PifC influences the production of bacteriochlorophyll and photosynthetic complexes (40).…”
Section: Discussionmentioning
confidence: 99%
“…The 2.3-kb E. coli relA-encoding EcoRIBamHI fragment from pALS 10 (a gift from M. Cashel, National Institutes of Health, Bethesda, MD) was inserted into corresponding sites of pMSI27, yielding pMS129. The resulting 2.8-kb HindlII fragment, which now contains the E. coli relA gene behind the M. xanthus carQRS promoter, was inserted into the HindlII site of pPLH343 (Kalman et al 1994), giving rise to pMS132. This plasmid contains the kanamycin resistance gene and the Mx8 phage attachment site, which allows for site-specific recombination within the M. xanthus genome.…”
Section: Strains Phages Plasmids and Genetic Manipulationsmentioning
confidence: 99%
“…The PifC sequence was compared with the IF3 and Dsg sequences of E. coli and M. xanthus (respective1y)which have both been shown to serve as initiation factors during translation and which themselves exhibit 48.9% identity (66.9% similarity; Fig. 3) (Sacerdot et al, 1982;Cheng et al, 1994;Kalman et al, 1994). Alignment of the R. sphaeroides PifC sequence with E. coli IF3 demonstrated a high level of overall similarity between the two sequences: 60.1 % identity; 78.6% similarity (Fig.…”
Section: Analysis Of the Predicted Pifc Proteinmentioning
confidence: 98%
“…Buckingham et al, 1990;Phillips-Jones et al, 1993, 199.5). Interestingly, recent studies of Myxucoccm X U I Z I~M S have revealed the importance of a translation initiation factor 3 in the regulation of developmental processes in bacteria Kalman et al, 1994). These studies showed that the Dsg IF3 protein not only performs some of the functions of an IF3 , but also has a specific selective role in fruiting body development and sporulation in this organism .…”
Section: Url: Http://wwwleedsacuk/mbiologymentioning
confidence: 99%